Aerosol size distribution derived from 355-nm and 532-nm Mie lidar signals - Vallar, Edgar A. (Animo Repository, 2006)
A Lookup Table (LUT) was generated using eleven aerosol size distributions (ASD) (from urban to maritime with 9 logarithmic increments in between them). In the computations, aerosol size ranged from 0.001-10μm with 1.40 to 1.60 real and 0.000-0.030 imaginary refractive indices for the 355-nm and 532-nm LIDAR wavelengths. The extinction coefficients (õ)EXPT were calculated for the LIDAR data using Fernald’s inversion method. The ASD in the De La Salle University area was determined by comparing (õ532/õ355)EXPT to (õ532/õ355)THEO values found in the LUT. Results show that the ASD is affected by local meteorological conditions and by man’s activities (e.g., fireworks during New Year’s eve).